2013
DOI: 10.1016/b978-0-12-407190-2.00016-2
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 (Forkhead box M1) in Tumorigenesis

Abstract: FOXM1 (Forkhead box M1) is a typical proliferation-associated transcription factor and is also intimately involved in tumorigenesis. FOXM1 stimulates cell proliferation and cell cycle progression by promoting the entry into S-phase and M-phase. Additionally, FOXM1 is required for proper execution of mitosis. In accordance with its role in stimulation of cell proliferation, FOXM1 exhibits a proliferation-specific expression pattern and its expression is regulated by proliferation and anti-proliferation signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(71 citation statements)
references
References 1,537 publications
2
65
0
Order By: Relevance
“…Similarly, we found that depletion of FOXM1 by transfection with FOXM1 shRNA could suppress cell growth, invasion and metastasis. Several studies have shown that FOXM1 could promote cell growth, invasion and metastasis in various cell types [4,5,24,25]. Here, we reached the same conclusion in EOC.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, we found that depletion of FOXM1 by transfection with FOXM1 shRNA could suppress cell growth, invasion and metastasis. Several studies have shown that FOXM1 could promote cell growth, invasion and metastasis in various cell types [4,5,24,25]. Here, we reached the same conclusion in EOC.…”
Section: Discussionsupporting
confidence: 87%
“…55 Plk1 is involved in a positive feedback loop with FoxM1, where Plk1-dependent phosphorylation is required for efficient FoxM1 activation, which in turn is required for expression of multiple mitotic regulators, including Plk1. 52 Interestingly, proteasome inhibitors have been shown to suppress FoxM1 transcriptional activity, suggesting that proteasome-dependent degradation may confer a level of indirect regulation to Plk1 overexpression in human carcinomas.…”
Section: Resultsmentioning
confidence: 99%
“…Aurora A/B, Survivin, and CDC25B)(22, 23). FOXM1 is also required for a variety of cancer cell phenotypes including cell proliferation, mitotic progression, DNA damage repair, angiogenesis, and suppression of apoptosis(2427). Siomycin A treatment significantly decreased the proportions of FOXM1(+), MELK(+) cells in GBM tumorspheres in a dose dependent manner, suggesting that siomycin A may abrogate cancer-specific MELK signaling through disruption of MELK-driven FOXM1 transcriptional activity.…”
Section: Targeting Melkmentioning
confidence: 99%